DR. NETHIA MOHANA AWARDED THE L’OREAL-UNESCO RESEARCH GRANT FOR STUDY ON CANCER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 September 2016 – A lecturer from the Universiti Sains Malaysia (USM) School of Biological Sciences, Dr. Nethia Mohana has been selected to be the recipient of the research grant from L'oreal-UNESCO for Women in Science National Fellowship 2016 valued at RM30,000.